Beyond biomedical frontiers: Multidimensional applications of silk and its derived proteins in energy, environment, and agri-food systems - Huanyan Ma; Zhaoyang Wang; Meiliang Pan; Fengyang Hu; Guangdong Sun; Xiuling He (APL Materials)
As a natural protein-based biopolymer with millennia of application history, silk has evolved into a transformative material platform bridging sustainable technology and biological design. This review systematically examines the molecular origins and processing innovations of silk-derived proteins, focusing on five core material attributes: biocompatibility, controlled biodegradation, mechanical adaptability, optical transparency, and processability. Recent breakthroughs in genetic engineering (CRISPR-edited silkworms) and nanocomposite fabrication (carbon nanotube hybrids) are critically analyzed for their roles in overcoming historical limitations in batch consistency and functional integration. The application survey spans (1) flexible electronics utilizing silk’s dielectric tunability for epidermal sensors, (2) biophotonic devices exploiting humidity-responsive optical modulation, (3) environmental technologies for air/water purification, and (4) agricultural innovations through silkworm by-product valorization. Industrial translation challenges are methodically addressed, including sterilization-induced denaturation, long-term storage stability, and scalability constraints in electrospinning processes. Emerging opportunities in intelligent food packaging and implantable drug delivery systems are highlighted, with particular emphasis on closed-loop production models that transform sericulture waste into high-value biomaterials. The review concludes by outlining synergistic research directions combining synthetic biology, machine learning, and green chemistry to advance silk’s role in sustainable manufacturing paradigms.